Student Cognition in the Context of a Climate System: Global Warming and Greenhouse Effect - Handayani, Rifati Dina; Putra, Pramudya DA (Momentum: Physics Education Journal, 2019)
Education needs to emphasize more attention to environmental issues. The school is an active place to provide actual knowledge, skills, attitudes, and behavior towards environmental issues such as global warming dan the greenhouse effect. This study aimed to investigate seventh-grade students' cognition in the context of a climate system. This study was descriptive, involving the collection of qualitative data. These qualitative data were then analyzed for their content inductively to identify concepts and patterns of student responses. This study indicated that students believed that global warming caused by six factors involving the greenhouse effect, depletion of the ozone layer, fossil fuel usage, forest fires, use of chemicals, and industrial air pollution. Also, they convinced six segments of the global warming impacts: ocean, soil, air, plants and animals, humans, and weather and season changes. The student thought about the climate system was substantially linear, where the contribution of human activities caused global warming that finally have an impact on humans themselves.